Detection And Quantification Of Amphetamine Type Stimulants And Methadone In Hair Using Liquid Chromatrography Triple Quadrupole (LC QQQ) Mass Spectrometry - Saad,, Khadijah Ali (2012)
Over the last decade, analysis of hair for drugs of abuse has emerged as one important alternative to urine drug test. Hair analysis has been proposed as a more suitable marker of past chronic drug intake as drugs are present in the free form; hair provides a longer detection window making it difficult to cheat ; it is easy to collect and the sample is stable at room temperature for long period of time . Hair analysis is increasingly used in pre-employment and employment screening, in the forensic sciences, doping control and clinical diagnostics.